Magnetic resonance imaging parameters relate with recovery time from muscle strain among professional football players - Nagamoto, H. (Translational Sports Medicine, 2020)
The purpose of this study was to investigate the relationship between imaging parameters of magnetic resonance imaging and recovery time from muscle strain of the lower extremities among professional football players. A total of 42 injuries from 24 male professional football players, who sustained lower extremity muscle strain, were included in the study. The longitudinal length of the injury and percentage of cross-sectional involvement were measured using the magnetic resonance imaging. The percentage of the cross-sectional involvement was defined as (a) under 25%, (b) over 25 to 50%, (c) over 50%-75%, and (d) over 75%. Imaging parameters were statistically analyzed between recovery time. Average recovery time was 22.2 days. The most injured muscle was the biceps femoris with 21 cases, 50%. The average longitudinal length of the injury was 10.7 cm. Average recovery time correlated significantly with the longitudinal length of the injury. Average recovery time became significantly greater among players with the cross-sectional involvement of over 50% compared with the players with percentage under 25%. Imaging parameters of longitudinal length and percentage of cross-sectional involvement related to recovery time until return to play from lower extremity muscle strain among professional football players.